FUNGSI KESENIAN RABANEA DALAM PESTA PERKAWINAN DI NAGARI SARIK ALAHAN TIGO KECAMATAN HILIRAN GUMANTI KABUPATEN SOLOK - Yoni Irawandi; Marzam Marzam; Yensharti Yensharti (SENDRATASIK UNP, 2013)
Abstract   This research discussed about the function of traditional art, Rabanea, in the wedding party in Nagari Sarik Alahan Tigo, Sub-district Hiliran Gumanti, Solok Regency. The topic was chosen because the researcher wanted to get description about the function of Rabanea in Nagari Sarik Alahan Tigo used in wedding party. It was a qualitative research with a descriptive analysis method. The data were collected through library studies, observation, interview, recording and photography. The rabanea is presented by using rabanea musical instruments as the accompaniment of poems in barzanji book and  four rhyme poetry in Minangkabaunese. Rabanea is used in traditional ceremony and religious matters, for example, in wedding ceremony. The use of rabanea is arranged by niniak mamak nan balimo (the five of traditional leaders) who stay in Nagari Sarik Alahan Tigo. Viewing the role of rabanea especially in wedding party, it can be concluded that the functions of Rabanea are as communication tool, entertainment, cultural inheritance, social and religious institution establishement, and the function related to spiritual and economical income.   Keyword:  Function, rabanea, wedding party